Trastuzumab-mediated selective delivery for platinum drug to HER2-positive breast cancer cells. Issue 9 (October 2015) - Huang, Rong; Sun, Yu; Gao, Qihe; Wang, Qiucui; Sun, Baiwang
Abstract : Oxaliplatin is used widely as an anticancer drug for clinical treatment. However, its applications are limited because of its poor selectivity. In this work, we described the design, synthesis, and characterization of conjugates combining trastuzumab with a platinum (IV) analog of oxaliplatin, in which the trastuzumab acted as an active targeting agent for HER2-positive cancer cells. Indirect enzyme-linked immunosorbent assay and immunofluorescence study indicated the platinum (IV)–trastuzumab conjugates retained specific binding activity to HER2 overexpressed SK-BR-3 cells. In the presence of ascorbic acid, platinum (IV)–trastuzumab conjugates were reduced to platinum (II) analogs, which could bind to and unwind PUC19 DNA in a manner similar to oxaliplatin. The cytotoxic study was tested on three breast cell lines: SK-BR-3, MCF-7, and MDA-MB-231. Platinum (IV)–trastuzumab conjugates showed promising antiproliferative activity against SK-BR-3 cells, but significantly decreased the inhibition to MDA-MB-231 and MCF-7 cells. The flow cytometric analysis showed that the conjugates arrested the cell cycle mainly at the G2/M phase and killed the cells through an apoptotic pathway. Abstract : Supplemental Digital Content is available in the text.